Place, identity and everyday life in a globalizing world - Perkins, Harvey C.; Thorns, David C. (Palgrave Macmillan, 2012)
"How do our everyday experiences and environmentsinform who we are? Covering hot topics, from virtual spaces to migration, this book connects daily life and identity with broader structural and global processes. With vivid examples highlighting the interdependence of place and society, it is a key text across the social sciences."-- Publisher's website